2012
DOI: 10.1186/1471-2202-13-116
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125b orchestrates cell proliferation, differentiation and migration in neural stem/progenitor cells by targeting Nestin

Abstract: BackgroundThe emerging concept is that microRNAs (miRNAs) play a central role in controlling stem cell self-renewal and fate determination by regulating the expression of stem cell regulators. miR-125b, one of neuronal miRNAs, recently was found to be necessary for neural differentiation of neural stem/progenitor cells (NS/PCs). However, the other specific biological role of miR-125b in NS/PCs is little known. We used rat NS/PCs as a model system to study the role of miR-125b in governing the behavior of NS/PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…miRNA-181a is rich in mature nerve cells and bioinformatic analysis has revealed that the cAMP response element-binding protein 1 (CREB1) mRNA 3'-UTR contains a complementary sequence to the miR-181a seed region. CREB1 is a key nuclear factor highly expressed in hippocampal neurons on which numerous signaling pathways converge (32)(33)(34). In the present study, the expression levels of these miRNAs were found to be significantly affected by sevoflurane and/or propofol anesthesia; therefore, general anesthesia may affect these cell signaling pathways, including synaptic plasticity and memory consolidation.…”
Section: Discussionmentioning
confidence: 49%
“…miRNA-181a is rich in mature nerve cells and bioinformatic analysis has revealed that the cAMP response element-binding protein 1 (CREB1) mRNA 3'-UTR contains a complementary sequence to the miR-181a seed region. CREB1 is a key nuclear factor highly expressed in hippocampal neurons on which numerous signaling pathways converge (32)(33)(34). In the present study, the expression levels of these miRNAs were found to be significantly affected by sevoflurane and/or propofol anesthesia; therefore, general anesthesia may affect these cell signaling pathways, including synaptic plasticity and memory consolidation.…”
Section: Discussionmentioning
confidence: 49%
“…MiR-125b target NES gene in neural stem cell [46] and it can target NES gene in SH-SY5Y cells also (Data not shown). Downregulation of NES gene after DC and RA treatment may be due to the combined effect of miR-432 and miR-125b.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, several other miRs have also been revealed to mediate the proliferation of neural cells. The overexpression of miR-125b, for example, inhibited the proliferation of neural stem/progenitor cells (22), and miR-34a was revealed to enhance cell proliferation and function of newly generated neurons, as well as improve behavioral outcomes (23). Furthermore, as patients with AD are characterized by learning and memory deficits (24), SAMP8 mice were used to investigate the effect of miR-135b on learning and memory behaviors in the present study.…”
Section: Discussionmentioning
confidence: 95%